P-Glycoprotein: One Mechanism, Many Tasks and the Consequences for Pharmacotherapy of Cancers - Seelig, Anna (Frontiers in Oncology, 2020)
P-glycoprotein or multidrug resistance protein (MDR1) is an adenosine triphosphate (ATP) binding cassette transporter (ABCB1) best known for being an obstacle to successful pharmacotherapy of cancers. It prevents cellular uptake of a large number of structurally and functionally diverse compounds, including the majority of cancer therapeutics, and in this way causes multidrug resistance. Systemic inhibition of P-glycoprotein for overcoming multidrug resistance however failed in clinical settings. As a way forward in the face of this outcome, we first suggest to broaden the view on P-glycoprotein function, by including its role in immunity, and by taking into account the metabolic pathways that control its expression. In a second part of this review, we discuss the mechanism by which P-glycoprotein is able to accomplishes its different tasks, and show that quantitative analysis of substrate transport and binding yield a set of thumb rules that allow predicting whether a compound is a modulator, substrate, inhibitor, or inducer of P-glycoprotein. In a third part, by way of example, these thumb rules are tested with a set of drugs (inhibiting the nuclear factor-κB) which has been previously repurposed for cancer therapy.